The beneﬁts and challenges of implementing service-learning in an advanced instructional design and technology curricula: implications for teaching professional courses - Yusop, F.D. (2013)

(untitled)
This paper reports on the beneﬁts and challenges of integrating service-learning pedagogy into a professional course taught at a US Midwestern university. Data were collected via observations, interviews and analyses of students’ online discussions, written reﬂections, and project work. Findings revealed that the service-learning approach improves academic learning, increases motivation to learn and serve, escalates civic values and develops a sense of concern over broader social issues. Most importantly, it prepares students to be civic-minded professionals who are concerned with the betterment of society. Additionally, the authentic and open nature of service-learning was found to contribute to intense group conﬂicts Suggestions to eliminate such challenges are also discussed.